2022
DOI: 10.1093/molehr/gaac019
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for TET-mediated DNA demethylation as an epigenetic alteration in cumulus granulosa cells of women with polycystic ovary syndrome

Abstract: Peripheral and tissue-specific alterations in global DNA methylation (5mC) and hydroxymethylation (5hmC) profiles have been charted as biomarkers for disease prediction and as hallmarks of dysregulated localized gene networks. Global and gene-specific epigenetic alterations in the 5mC profiles have shown widespread implications in etiology of polycystic ovary syndrome (PCOS). However, there has been no study in PCOS that integrates the quantification of 5mC and 5hmC signatures alongside the expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Previous studies have reported ALYREF expression in ovarian cancer [38] [39]. AGO2 dysfunction plays a signi cant role in obesity in PCOS patients [40,41] and TET2 may indicate epigenetic alterations in the cumulus granulosa cells of women with PCOS [42]. Conversely, YTHDF2 is believed to suppress tumor growth through immune reprogramming to enhance CD8 + T cell-mediated antitumor immunity [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported ALYREF expression in ovarian cancer [38] [39]. AGO2 dysfunction plays a signi cant role in obesity in PCOS patients [40,41] and TET2 may indicate epigenetic alterations in the cumulus granulosa cells of women with PCOS [42]. Conversely, YTHDF2 is believed to suppress tumor growth through immune reprogramming to enhance CD8 + T cell-mediated antitumor immunity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Pathway enrichment analyses indicated the involvement of various pathways, including the Notch, Wnt, IL2, and IL6 signaling pathways. Recent studies have further demonstrated Notch signaling plays a signi cant role in the ovary [42,47,48] ,while Wnt signaling has been linked to the effect of speci c treatments for PCOS [44]. Further, a clinical study found that letrozole activated the Wnt/B-catenin pathway, leading to full endometrial proliferation in women with PCOS receiving letrozole [49].IL-6 signal,ing is associated with in ammation in ovarian syndrome [50].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment of these third-generation prenatal Anti-Mullerian Hormone (AMH) exposed mice female offspring with methylating medication can reverse their PCOS-like neuroendocrine and metabolic alterations [ 16 ]. Sagvekar et al [ 17 ] revealed that the alternation in transcriptional regulation of translocation methylcytosine dioxygenases (TETs) and DNA methyltransferases 3A (DNMT3A) may contribute to DNA methylation changes in cumulus granulosa cells of PCOS women. Nowadays, an increasing number of genome-wide association studies on prenatal hyperandrogenism-induced methylation in the ovarian tissue of PCOS rats are emerging, which will provide a more experimental basis for future PCOS treatment.…”
Section: Challenges and Possible Solutions Of Pcosmentioning
confidence: 99%